ENHANCING TAX COMPLIANCE THROUGH DIGITAL TRANSFORMATION: EVIDENCE FROM CORPORATE TAXPAYERS' USAGE OF E-BUPOT - Faisol, Moh.; Norsain, Norsain (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2024)
Digital transformation facilitates and accelerates taxpayers in withholding/collecting taxes and registering, reporting, and paying taxes. This research aims at understanding the use of E-Bupot in the tax withholding/collection process to improve tax compliance for corporate tax players in the Sumenep Regency. The authors used the phenomenology method by conducting interviews with two informants and then interpreting and explaining the actions or experiences of taxpayers. This research concluded that using information technology with E-Bupot was more practical in tax withholding. E-Bupot also sped up the tax collection process and minimized costs, including file storage because it did not use paper. The implication was that information technology could be an alternative to increase taxpayer compliance because technology had become a part of the lives of Indonesian people.